Reduced arterial compliance in patients with psychiatric diagnoses - Mathew Koola, Maju (2012)
BACKGROUND: Peripheral arterial compliance is a measure of elasticity of the arteries that has been found to be a robust predictor of prevalent arteriosclerosis as well as incident stroke and myocardial infarction. Psychiatric diagnoses and second generation antipsychotics may contribute to cardiovascular risk and stroke, but effects on peripheral arterial compliance are unknown. This study compared peripheral arterial compliance in healthy male controls to male patients with psychiatric diagnoses who were treated with quetiapine or risperidone or off antipsychotics at time of testing. METHODS: The groups consisted of 63 patients with mental illness taking quetiapine, risperidone, or no antipsychotics. There were 111 males in the control group. Mean thigh and calf arterial compliance among four groups were compared by ANCOVA, adjusting for body mass index and Framingham Risk Score. All patients were also compared to the control group. Compliance was measured with a computerized plethysmography device. RESULTS: Patients (n = 63) had significantly lower arterial compliance in both thigh and calf than the controls. Arterial compliance in the calf was significantly lower in the subgroups of quetiapine (n=16) and risperidone (n=19) treated, and in unmedicated (n=28) patients than in controls. In the thigh, patients taking either quetiapine or risperidone had significantly lower arterial compliance than controls. These subgroups did not differ from each other in arterial compliance. CONCLUSION: The presence of psychiatric diagnoses is associated with reduced arterial compliance. A large study may berequired tomeasure any specific affects of antipsychotics such as quetiapine and risperidone on compliance compared to controls.